CORRELATION OF WAIST HIP CIRCUMFERENCE RATIO WITH FASTING BLOOD GLUCOSE CONSENTRATION AT THE AGE OF 30-65 YEARS IN THE DISTRICT OF KEDIRI - Cien Stevani; Nita Kurniawati; Dyana Sarvasti (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: The World Health Organization (WHO) stated that obesity is a world epidemic. According to basic health research in 2018, the prevalence of central obesity in the population aged 15 years in Kediri Regency/City has a higher prevalence compared to the average prevalence in East Java Province. The waist hip circumference ratio is one of the anthropometric calculations that can be used to assess central obesity. The high prevalence of central obesity in Indonesia is closely related to the incidence of non-communicable diseases, including diabetes mellitus. However, only 25% of people with diabetes mellitus know that they have diabetes. Routine blood sugar checks for residents in districts/cities, especially in the city of Kediri, are also at a low level of 3.6%, so this is the reason for conducting this study.Objective: To study the correlation between waist hip circumference ratio with fasting blood glucose concentration at the age of 30-65 years in the District of Kediri.Method: Cross sectional observational analytical research approach. Sampling using consecutive sampling. Testing the correlation between two variables using the Spearman correlation test. The correlation between variables is considered significant if the p value <0.05 is obtained.Result: This research was conducted in Sonorejo Village, Grogol District, Kediri Regency, East Java on August 10 – August 12, 2021. Otained 40 respondents with an age range of 30-65 years. The correlation between waist hip circumference ratio with fasting blood glucose consentration was not statistically significant (p=0,453). The correlation value of 0.122 indicates a very weak correlation strength and is not clinically significant.Conclusion: There is no correlation between waist hip circumference ratio with fasting blood glucose concentration at the age of 30-65 years in the District of Kediri. Keywords:Waist hip circumference ratio, fasting blood glucose, Kediri.